(untitled) (Web of Teachers: Inderscience Research, 2024)
At the present stage of world economic development, the development of features of economic policy contributing to the socio-economic sustainable development of the regions and their effective implementation is becoming increasingly important. Increasing the opportunities for attracting foreign direct investment to sectors and sectors of the economy, modernization of industrial enterprises, the introduction of advanced foreign equipment and technologies into production is largely linked to the creation of special economic zones, including small industrial zones. Consequently, the chosen research topic becomes relevant to the present day.